2002
DOI: 10.1152/jn.2002.88.1.438
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-Visual Interactions Subserving Goal-Directed Saccades in a Complex Scene

Abstract: This study addresses the integration of auditory and visual stimuli subserving the generation of saccades in a complex scene. Previous studies have shown that saccadic reaction times (SRTs) to combined auditory-visual stimuli are reduced when compared with SRTs to either stimulus alone. However, these results have been typically obtained with high-intensity stimuli distributed over a limited number of positions in the horizontal plane. It is less clear how auditory-visual interactions influence saccades under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
147
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 45 publications
28
147
0
Order By: Relevance
“…In the latter case, the bimodal performance is limited by the visual system, and the additional auditory input does not substantially increase the performance. The results are consistent with those reported by Corneil et al (2002), using a very different experimental paradigm and task. Corneil et al measured saccadic eye movements in response to auditory, visual, and bimodal stimuli; they found that the accuracy of the bimodally driven saccades is determined largely by the accuracy of the visually initiated saccades and not by the auditory ones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the latter case, the bimodal performance is limited by the visual system, and the additional auditory input does not substantially increase the performance. The results are consistent with those reported by Corneil et al (2002), using a very different experimental paradigm and task. Corneil et al measured saccadic eye movements in response to auditory, visual, and bimodal stimuli; they found that the accuracy of the bimodally driven saccades is determined largely by the accuracy of the visually initiated saccades and not by the auditory ones.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, if the object is hidden for a short period (Condition 2) and the task therefore requires the extrapolation of motion speed over a temporal and spatial period, the facilitation due to both sensory inputs is almost absent, and the bimodal performance is limited by the visual performance. rooij, Munoz, & Van Opstal, 2002) corroborated previous behavioral and electrophysiological findings (Stein & Meredith, 1993) by demonstrating that the improvement in SRTs is optimal when the auditory and the visual stimuli are synchronized. EEG studies, in combination with behavioral RT measurements (Molholm et al, 2002), have confirmed these behavioral findings by demonstrating shorter bimodal RTs than unimodal ones; this facilitation can be accounted for by neural summation, rather than by an independent decision model (race model).…”
supporting
confidence: 82%
“…When audiovisual stimuli are spatially aligned within~20°of vertical separation and observers have to orient to an auditory or a visual target, both latency and accuracy improve, relative to the unisensory and misaligned conditions. This thus indicates a rule of "best-of-both-worlds" (Corneil, Van Wanrooij, Munoz & Van Opstal, 2002), in which observers benefit from the spatial accuracy provided by the visual component, and a shorter latency onset that is triggered by the auditory component. Prior expectations about the audiovisual spatial alignment also matter: That is, participants are faster on aligned trials when 100 % of the trials are aligned, rather than only 10 % of the trials (Van Wanrooij, Bremen & Van Opstal, 2010), thus suggesting that audiovisual binding may have a dynamic component that depends on the evidence for stimulus congruency as acquired from prior experience.…”
Section: Bayesian Approachesmentioning
confidence: 74%
“…This may be one reason why it has not shown up in most behavioral studies with humans. Corneil, Van Wanrooij, Munoz, and Van Opstal (2002) suggested some further reasons. First, in many studies, the stimuli may not have been close enough to threshold.…”
Section: Discussionmentioning
confidence: 99%